Pengembangan alat peraga dan modul Internet of Things dengan pendekatan define-measure-analyze-design-verify untuk mendukung aktivitas pembelajaran - Pramudika, Gregorios Ferrari; Nugraha, Brilianta Budi (Universitas Atma Jaya Yogyakarta, 2025)
The Industrial Era 4.0 requires someone to have skills that are relevant to the pillars of Industry 4.0, one of which is digitalization, including the Internet of Things (IoT). Atma Jaya University Yogyakarta through the Industrial Engineering Study Program has Industrial Automation and Industrial Automation Practicum courses as a forum to provide competence in the field of mechatronic systems in industry. One of the materials taught in the course is IoT. However, learning IoT material is considered not optimal because the Automation Laboratory does not yet have appropriate teaching aids and modules. This study aims to develop IoT teaching aids and practicum modules using the DMADV (define, measure, analyze, design, verify) approach. This methodology focuses on customer needs obtained through interviews and Kano surveys, then used as a basis for designing designs with morphological maps. The resulting teaching aid is a Smart Warehouse, a miniature automatic warehouse for storing wax products from a mini factory. This tool consists of sensors, stack lights, PLCs, SCADA as server applications, and client applications. This Smart Warehouse can carry out simple warehousing activities automatically, and is equipped with practicum modules and manual books to facilitate its use.